Efektifitas Pendampingan Minum Tablet Tambah Darah (TTD) Oleh Kader Posyandu terhadap Peningkatan Kadar Hb Ibu Hamil di Puskesmas Kota Palangka Raya - Seri Wahyuni (Jurnal Surya Medika (JSM), 2018)
Anemia is one of the indirect causes of maternal mortality. The Government of Indonesia has made efforts to overcome anemia, including by giving iron tablets to pregnant women. To improve maternal compliance in consuming iron tablet healthcare workers should include family/cadres in the supervision of food and medicine. This study aims to know the effectiveness of accompaniment drinking iron tablet By Cadres Against Increasing Hb Level of Pregnant Women at Puskesmas Kota Palangka Raya. This research is a quasi-experimental design using "nonrandomized control group pretest-posttest design" approach. Sampling technique total sampling is with the number of samples of 62 people divided into 2 groups, 31 intervention groups, and 31 control groups. In the intervention group involving cadres as moderate blood-boosting drink companions in the control group without blood-boosting companions. The analysis technique used for the intervention and control group is using the Wilcoxon test. The result of intervention group statistic test get p-value = 0,000 (